2017
DOI: 10.1007/s00394-016-1370-2
|View full text |Cite
|
Sign up to set email alerts
|

Iodine intake as a risk factor for BRAF mutations in papillary thyroid cancer patients from an iodine-replete area

Abstract: Relatively low iodine intake and more than excessive iodine intake seem to be significant risk factors for the occurrence of BRAF mutations in the thyroid and, therefore, may be risk factors for the development of PTC in an iodine-replete area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 25 publications
4
42
1
2
Order By: Relevance
“…Our finding is similar to those reported in PTC patients diagnosed in cities from other Brazilian regions, such as Goiânia (74/116; 63,8%) and Porto Alegre (19/32; 59,4%) (19,20). Some studies have implied that the increased occurrence of BRAF (V600E) mutation in PTC may be associated with high dietary iodine intake (21). We found in a previous study from our laboratory a high risk of excessive nutritional iodine intake among schoolchildren in Salvador (22), a coastal Brazilian city.…”
Section: Discussionsupporting
confidence: 89%
“…Our finding is similar to those reported in PTC patients diagnosed in cities from other Brazilian regions, such as Goiânia (74/116; 63,8%) and Porto Alegre (19/32; 59,4%) (19,20). Some studies have implied that the increased occurrence of BRAF (V600E) mutation in PTC may be associated with high dietary iodine intake (21). We found in a previous study from our laboratory a high risk of excessive nutritional iodine intake among schoolchildren in Salvador (22), a coastal Brazilian city.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, in a Korean population that chronically consumes iodine-rich foods, Kim et al demonstrated that BRAF mutations in PTC were more frequent in subjects with either low (urinary iodine concentration, UIC < 300 µg/L) or excessive iodine intakes (UIC ≥ 500 µg/L) [26]. …”
Section: Eating Habitsmentioning
confidence: 99%
“…Так, дефіцит йоду може призводити до превалювання фолікулярного типу РЩЗ, а при проведені йодної профілактики, навпаки -папілярної, про що свідчать дослідження Dong W. et al (2013) та Kim H.J. et al (2017) [91,92]. Пов'язаний з йодом зсув від фолікулярного до папілярного гістологічного типу може бути зумовлений частотою мутації BRAF (V600E) [92].…”
Section: в п о м о щ ь п р а к т и ч е с к о м у в р а ч уunclassified
“…et al (2017) [91,92]. Пов'язаний з йодом зсув від фолікулярного до папілярного гістологічного типу може бути зумовлений частотою мутації BRAF (V600E) [92]. Один з недавніх мета-аналізів, проведений Cao L.Z.…”
Section: в п о м о щ ь п р а к т и ч е с к о м у в р а ч уunclassified